2005
DOI: 10.1200/jco.2005.05.180
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry Identifies Carriers of Mismatch Repair Gene Defects Causing Hereditary Nonpolyposis Colorectal Cancer

Abstract: Wide clinical criteria to select HNPCC kindreds, followed by immunohistochemistry of tumor material from one affected person in each family, had high sensitivity and specificity to predict MMR mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…This suggested that the cutoff values are required in both functional level and protein level for overall evaluation. Recent studies have indicated that the immunohistochemical analysis of MMR proteins is one of the most efficient and sensitive screening method to detect abnormalities in MMR proteins (40,41). In our data, in vitro MMR activities were impaired without reducing MLH1 protein levels in some MLH1 missense variants.…”
Section: Discussionsupporting
confidence: 48%
“…This suggested that the cutoff values are required in both functional level and protein level for overall evaluation. Recent studies have indicated that the immunohistochemical analysis of MMR proteins is one of the most efficient and sensitive screening method to detect abnormalities in MMR proteins (40,41). In our data, in vitro MMR activities were impaired without reducing MLH1 protein levels in some MLH1 missense variants.…”
Section: Discussionsupporting
confidence: 48%
“…With a reliable immunohistochemical method, in most cases, only the mutated gene would be screened. This methodology has recently been demonstrated to be useful in the identification of carriers of mutations in the mismatch repair genes associated with hereditary non-polyposis colorectal cancer (Stormorken et al 2005).…”
mentioning
confidence: 99%
“…Therefore, by revealing the presence of MLH1 or MSH2 LOH in an MSI-positive tumor, our method could eliminate further need for IHC analysis and appreciably lower the cost of prescreening in a nonnegligible percentage of cases. This approach could be especially useful when technical difficulties arise in the execution and/or interpretation of IHC assays (32)(33)(34)(35)(36)(37). The final results of IHC analyses are influenced by several factors, including those related to preparing the FFPE sample (type of fixative, fixation times, temperatures reached during the embedding procedure).…”
Section: Discussionmentioning
confidence: 99%